Morphological and pathogenic characterization of Fusarium species causing common bean root rot in Uganda - Erima, Samuel; Nyine, Moses; Edema, Richard; Nkuboye, Allan; Nakibuule, Justine; Paparu, Pamela (Journal of Scientific Agriculture, 2024)
Fusarium root rot (FRR) of common bean occurs in Africa, Central and South America, and causes yield losses of up to 86%. Recently, FRR-like wilt symptoms were observed in Uganda’s agroecology zones. To identify the causal pathogen, we conducted surveys in seven agroecology zones to determine the prevalence and incidence of the reported disease. During the surveys, diseased roots were collected for pathogen isolation. Fungal strains were characterized using colony color, mycelial growth rate and microscopic structures such as conidia and microconidia. The pathogenicity of 99 strains on five bean varieties was determined in artificially inoculated soils in the screenhouse. Based on field symptoms, the observed wilting was identified to be Fusarium root rot, the prevalence of which varied across agroecologies, with the highest (95%) in the Karamoja pastoral zone (KP) and the lowest (40%) in West Nile farming system (WN). Similarly, the incidence of FRR was highest (87%) in KP, and lowest (20%) in WN. Fusarium strains differed in growth rate, colony color, shape and size of microscopic structures. All evaluated strains were pathogenic on common bean and caused severities of 0.9 to 98.3%. Further studies are required to identify the isolated strains at the species level using molecular tools.